The Declension of a Story:: Narrative Structure in Howard O’Hagan’s Tay John - Hingston, Kylee-Anne (Studies in Canadian Literature / Études en littérature canadienne, 2005)
Many critics of Howard O'Hagan's Tay John assume that storytelling is a process in which simple events are altered through tale until they transmogrify into legend. This reading is challenged by the section titles, which devolve from "Legend" to "Hearsay" to "Evidence - Without A Finding," implying that factual evidence is a degeneration from pure legend. Tay John reveals a Platonic differentiation between storytelling and story; storytelling is the shadow's tangible evidence of an intangible, true story, or legend, which can never be absolutely known or represented by one tale. Tay John himself is meant to represent the intangible essence of story. Through images of (re)birth, he is seen as always emerging into forms of familiar stories superimposed upon him. He mirrors but never contains his full story. Ultimately, Tay John's spirit and body refuse narration. However, Tay John emphasizes the importance of storytelling while recognizing its limitations.